Multirow arrangement of laterally loaded passive piles in sand - Mujah, Donovan; Hazarika, H.; Watanabe, N.; Ahmad, F. (Research Publishing, 2013)
The use of reinforcement steel bars and passive piles are the oldest method adopted in slope stability counter measure in which, their reinforcing mechanisms are designed to function independently. This research proposes new kind of piles, hereafter called small diameter steel piles (SDSP), which are able to resist both lateral and vertical forces in slope stabilization measure. This paper intends to shade light on the prevention mechanism of SDSP and how multirow arrangement of piles affects the reinforced slope failure in slope failure prevention. To that end, laboratory scale experiment using direct shear test was performed to replicate the lateral soil movement induced by landslide in which, Toyoura sand and aluminum rods were used to imitate ground condition and steel piles respectively. Likewise, finite element analysis (FEA) employing Mohr-Coulomb’s elastic-perfectly plastic soil model was also carried out to simulate the experiment. In this study, the effect of the ground density and cross sections of the reinforcing rods in piles’ prevention mechanism were considered. Based on the results, it was found that the failure mode of dense ground is governed by soil’s shearing resistance mobilized at a higher strain, while bending stiffness of the reinforcing material is more dominant in loose ground regardless of the piles arrangements.